A functional hydrogel film attached with a 2D Au nanosphere array and its ultrahigh optical diffraction intensity as a visualized sensor. Issue 11 (29th February 2016) - Men, Dandan; Zhou, Fei; Hang, Lifeng; Li, Xinyang; Duan, Guotao; Cai, Weiping; Li, Yue
Abstract : Free-standing 2D Au nanosphere array/hydrogel composite films on an ordinary quartz substrate demonstrate a strong diffraction signal, which could improve their practical applications in visual detection. Abstract : Free-standing 2D Au nanosphere array/hydrogel composite sensing films were prepared by attaching a 2D Au nanosphere array onto a polyacrylic acid (PAAc) hydrogel film, which could be used as visualized sensors. These 2D Au nanosphere array/hydrogel composite films displayed visually diffraction color and much stronger diffraction intensity due to their periodic structures and large scattering cross-section of the Au nanospheres. Their diffraction intensity was increased by more than one order of magnitude (88 times) compared to that of 2D PS sphere array/hydrogel composite films to external stimuli, which is useful for visual observation by the naked eye and further optical characterization. Such 2D Au nanosphere array/hydrogel composite films exhibit ultrahigh diffraction intensity for them to be used for the visual determination of an analyte. The presented strategy could be extended to develop different visualized sensors based on various functional hydrogel films.